Effect Of Listeria monocytogenes Experimentally Infected Dosage In The Percentages Of Broiler Chicks Serum Proteins: Faris A. Al-Obaidi, , Muthana M. , Nagham M. Al-Jebouri , and Shahrazad A. Al-ShadeediEman A. Qazaz - Al-Obaidi, Faris A. (The Iraqi Journal of Veterinary Medicine, 2007)
This study has been conducted to study the effect of experimentallyinfected broiler chicks orally by two dosages of Listeria monocytogenes inthe percentages of serum protein of 30 broiler chicks at 7 and 15 days ofinfection . The birds randomly distributed into three treatments , T1 : controlgroup , T2 : chicks orally infected by 6 X 405 CFU of L. monocytogenes , T3: chicks orally infected by 34 X 4010 CFU of L. monocytogenes. The dataobtained revealed the following :-Percentages of serum Pre-albumin , Albumin , Total albumins and  -Globulin were decreased significantly (P<0.05) , in the same timePost_albumin ,  ,  - Globuluins and Total globulins increased significantly(P<0.05) in broiler chicks orally by the two dosages of L.monocytogenes (T2 and T3) compaired with control group (T1) after 7 daysof infection , whenas a significant (P<0.05) increase in immunoglobulinpercentage (- Globulin) with Transferrin in the same time other proteinsreturn to its normal percentages after 15 days of infection , which indicatedof development immunity and inhanced chicks health at this age . Nodifferences appeared in chicks serum protein due to the listeria infectiondosages in this study